MENINGKATKAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN INTERAKTIF BERBASIS TPACK PADA MATA PELAJARAN PKN KELAS VI SD NEGERI BANJARHARJO KALIBAWANG - Vuri Putri Yonatin; Sutrisna Wibawa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to see and determine the uses and benefits of TPACK-based Wordwall media in the science and science subject for class VI students at SDN banjarharjo Kalibawang. The method in this research is descriptive qualitative. The variable in this research is the use of Wordwall media (single variable). The research subjects were 8 students. Research data was obtained based on interviews and observations. Data analysis techniques are data reduction, data display, and verification. The results of this research are that there are significant benefits in using TPACK-. The conclusion of this research is that media is an interactive and effective media, using it makes students think more critically and students are not afraid of making mistakes, answering questions are more relaxed and not burdened because the questions with writing assignments. Apart from being easy and cheap to use, using this media requires a stable network condition and the ability to operate laptops and other devices well.